Music Therapy and Aromatherapy Interventions in Patients undergoing Hemodialysis: A Systematic Review - Sariati Sariati; Dwi Uswatun Sholikhah; Cahya Mustika Narendri; Gevi Melliya Sari; Qolbi Nur Qoidah Yahya (Universitas Airlangga, 2019)
Introduction: The number of patients with chronic kidney disease (CKD) who undergo hemodialysis is increasing every year. Various attempts have been made to maximize the process of hemodialysis, one of which is by providing complementary therapy with music as therapy and through the administration of aromatherapy. The aim of this study was to identify the effectiveness of the use of music therapy and aromatherapy in a patient diagnosed with chronic kidney disease undergoing hemodialysis.Methods: The literature review followed on from the identification of the interventions then the studies were identified by keyword according to the topic and title. There were 15 articles that discussed the effect of music therapy and aromatherapy on patients undergoing hemodialysis. The design RCT was 7 articles, 3 quasi-experimental articles, and 5 clinical trial articles.Results: Music can raise the endorphin and serotonin levels and reduce the catecholamine levels, so it can change the respiratory rate and oxygen saturation, improve their quality of sleep and reduce fatigue.Conclusion: Our findings indicate that music therapy and aromatherapy have a positive effect on patients with chronic kidney disease undergoing hemodialysis.